Evaluating the efficacy and safety of immune checkpoint inhibitors in first and second-line treatments for recurrent and metastatic head and neck squamous cell carcinoma: a systematic review and network meta-analysis of RCTs with a focus on PD-L1 expression - Chen, Wei; Wei, Qiance; Xiao, Tong; Lai, Jinghan; Huang, Mengmeng; Ma, Yueran; Zhang, Lili; Xue, Wenxin; Liu, Shui; Sun, Lichaoyue; Li, Wenshu; Bu, Zhijun; et al. (Frontiers in Immunology, 2025)
IntroductionThis study systematically reviewed and conducted a network meta-analysis to assess the efficacy and safety of first-line and second-line immunotherapy treatments for recurrent and metastatic head and neck squamous cell carcinoma (R/M HNSCC). The findings aim to provide robust evidence to guide clinical decision-making.MethodsWe conducted an comprehensive literature search in PubMed, Embase, Cochrane Library, and Web of Science. The outcome measures included overall survival (OS), progression-free survival (PFS), overall response rate (ORR), and grade 3 or higher adverse events (AEs ≥3). To compare the efficacy and safety of various first-line and second-line immunotherapy regimens for R/M HNSCC with different PD-L1 expression levels, we conducted a Bayesian network meta-analysis. This study is registered in the Prospective Register of Systematic Reviews (CRD42024551711).ResultsThis analysis included 9 randomized controlled trials (RCTs) involving 5,946 patients and seven immunotherapy regimens. Among patients with R/M HNSCC, pembrolizumab combined with chemotherapy as a first-line treatment was the only immunotherapy regimen to show a PFS benefit compared to SOC (HR = 0.92, 95% CI: 0.77–1.10); however, the difference was not statistically significant. Meanwhile, nivolumab provided the most pronounced OS benefit (HR=0.71,95%CI:0.52-0.98). Additionally, pembrolizumab exhibited the most favorable safety profile relative to SOC (OR=0.12, 95% CI: 0.05-0.29). In second-line therapy, nivolumab outperformed SOC in multiple aspects, including OS (HR=0.68, 95% CI: 0.54-0.86), ORR (OR=0.40, 95% CI: 0.17-0.95), and grade ≥3 adverse events (OR=0.32, 95% CI: 0.19-0.54). Subgroup analysis by PD-L1 expression revealed that nivolumab, compared to SOC, conferred the greatest OS benefit (HR=0.59, 95% CI: 0.34-1.00) as a first-line therapy in patients with PD-L1 expression ≥1%, while pembrolizumab combined with chemotherapy(pem-chemo) showed the most substantial PFS benefit (HR=0.82, 95% CI: 0.67-1.00). For patients with PD-L1 expression ≥20%, pem-chemo delivered the optimal OS (HR=0.60, 95% CI: 0.44-0.81) and PFS (HR=0.73, 95% CI: 0.55-0.97) outcomes compared to SOC. Furthermore, in patients with PD-L1 expression ≥1%, nivolumab as a second-line treatment demonstrated superior OS (HR=0.55, 95% CI: 0.39-0.78) and PFS (HR=0.59, 95% CI: 0.41-0.84) compared to SOC.ConclusionsThese results suggest that immunotherapy may improve survival outcomes compared to SOC for patients with R/M HNSCC, while maintaining a comparable safety profile. For patients, pembrolizumab combined with chemotherapy and nivolumab as first-line treatments may represent the most optimal options, with nivolumab also showing promise as a second-line therapy. In patients with PD-L1 expression ≥1% or ≥20%, pembrolizumab combined with chemotherapy may be the preferred first-line therapy, while nivolumab remains the most favorable second-line treatment.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024551711.